Aspects of Frequentism. Issue 3 (5th July 2018) - Caldwell, Allen
Abstract: Some aspects of the Frequentist approach to statistical data analysis are presented and discussed. The construction of confidence intervals for parameters is explained and made concrete with a detailed example. The intervals correspond to parameter ranges where the observed data is in a 'favored' part of the expected results distribution. Goodness‐of‐fit tests are defined similarly; here, a Bayesian argument is given for the usefulness of these tests. The possible over‐interpretation of Frequentist results is also discussed. Abstract : Some aspects of the Frequentist approach to statistical data analysis are presented and discussed. The construction of confidence intervals for parameters is explained and made concrete with a detailed example. Goodness‐of‐fit tests are defined similarly; here, a Bayesian argument is given for the usefulness of these tests. The possible over‐interpretation of Frequentist results is also discussed.